An Analysis of Students’ Difficulties in Writing Descriptive Text at Tenth Grade of Smk Negeri 4 Kota Jambi - Debby Ardila Tri Ramadan; Wennyta Wennyta; Suyadi Suyadi (Universitas Batanghari Jambi, 2021)
The purpose of this research is to analize students’ difficulties in writing descriptive text. The problem of this research is students’ difficulties in generic structure, language feature, lack of vocabulary and arranging sentences in writing descriptive text. The objective of this research is to identify the students’ difficulties in writing descriptive text. The research conducted at SMK Negeri 4 Jambi in academic years 2019/2020. The population of this research is tenth grade student of fashion class IV. The sample is all of the fashion class IV at the tenth grade which the total number of students are 33 female students. The type of the research is qualitative descriptive. The data were obtained by using online questionnaire by using google forms. Overall, the result of this research is 60% students have difficulties on language feature. While, 30% students have difficulties in generic structure which is as same as the students are who have limited vocabulary in writing descriptive text. Moreover, the biggest percentages which are majority of students have difficulties on arranging sentences to be paragraph.Keywords: An Analysis of Students’ Difficulties of Writing Descriptive Text.